MAKING OF CHEMICAL LITERACY ORIENTED CHEMICAL ADVENTURE LEARNING MEDIA IN ADDITIVE MATERIAL - Cindy Phangestu; Cucu Zenab Subarkah; Imelda Helsy (Gunung Djati Conference Series, 2021)
This research was motivated by the importance of a learning media that can improve students chemical literacy skills by connecting additive material with phenomena that occur in everyday life. This study aimed to produce an educational game in the form of chemical adventure media which has characteristics such as modified game rules from adventure games and monopoly, equipped with questions, obstacles in chemical literacy-oriented games which include the use of additives, impacts, consumption limits and Islamic view of good foods for consumption. This study used the Design Based Research (DBR) method. The validation test results of the chemical adventure media product were valid with an average rcount of 0.80, with 0.84 on the presentation aspect of the material content and 0.76 on the display aspect. This shows that the chemical adventure media is valid and can be used as a learning media.